COMBINED MEDICATIONS OF LOCAL ACTION IN THE TREATMENT OF PAIN AND SORE THROAT SYMPTOMS - M. I. Petrovskaya (Union of pediatricians of Russia, 2012)
For relief symptoms of pain and sore throat the prescription of combined topical preparations containing antiseptic and analgesic components is the most appropriate from the pathogenetic point of view. This article discusses the use of local therapy for the treatment of acute inflammatory diseases associated with pain, feeling a tickle in throat. The author introduces the local action drug, which has antiseptic and analgesic effects and is safe and effective in the symptomatic treatment of pharyngitis, tonsillitis and laryngitis in children older than 4 years.